Effects of nonpharmacological intervention on sleep quality in hemodialysis patients: A protocol for systematic review and meta-analysis. Issue 27 (9th July 2021) - Li, Hui; Zuo, Long; Long, Siyu; Li, Baifei
Abstract: Background: Nonpharmacological intervention can improve the sleep quality of hemodialysis patients. However, there are many types of nonpharmacological interventions, which makes it difficult to determine the best one. Therefore, this study carried out network meta-analysis to evaluate the effects of nonpharmacological intervention on sleep quality of hemodialysis patients, so as to provide evidence for the selection of the optimal nonpharmacological intervention for the improvement of sleep quality of hemodialysis patients clinically. Methods: Randomized controlled trials on the effects of nonpharmaceutical interventions on sleep quality in hemodialysis patients were conducted by searching English databases (PubMed, Cochrane Library, EMBASE, and Web of Science) and Chinese databases (Chinese Scientific Journal Database, China National Knowledge Infrastructure Database, Wanfang, and China Biomedical Literature Database) on computer. The retrieval time was from the establishment of the database to May 2021. Literature screening, data extraction, and evaluation of the risk of bias in the included studies were conducted independently by two researchers. Data analysis was performed with STATA14.0 and GEMTC 0.14.3 software. Results: We will disseminate the findings of this systematic review and meta-analysis via publications in peer-reviewed journals. Conclusions: This study will provide the best evidence-based evidence to support the effects of non-pharmacological interventions on sleep quality in hemodialysis patients. Ethics and dissemination: Ethical approval was not required for this study. The systematic review will be published in a peer-reviewed journal, presented at conferences, and shared on social media platforms. This review would be disseminated in a peer-reviewed journal or conference presentations. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/4BPKT.